Acute Eosinophilic Pneumonia Secondary to Menthol Cigarette Use: A Rare Phenomenon With a Review of Literature. (May 2020) - Harne, Prateek Suresh; Rao, Suman; Malik, Muhammad; Shepherd, Zachary
Idiopathic acute eosinophilic pneumonia (AEP) is a very rare disease with fewer than 200 cases reported. It has been hypothesized to be a hypersensitivity reaction to an unidentified antigen. The clinical presentation typically involves fever, nonproductive cough, shortness of breath, and bibasilar inspiratory crackles within the first week of antigen exposure. Chest imaging usually reveals bilateral reticular and/or ground-glass opacities. Bronchoalveolar lavage demonstrates >25% eosinophils. Corticosteroids are the mainstay of treatment with good results; however, optimum dose and length of treatment are unclear. We present a case of a 31-year-old male who presented with 2 days of shortness of breath, cough, pleuritic chest pain, fevers, chills, nausea, and poor appetite in the setting of initiation of menthol-flavored cigarettes 2 weeks before presentation. He rapidly progressed to respiratory failure requiring intubation despite broad antibiotic coverage. His course was complicated by severe acute respiratory distress syndrome, circulatory shock, and renal failure. He underwent bronchoalveolar lavage testing that revealed 60% eosinophils. He was treated with steroids and was subsequently extubated and discharged. Eosinophilic counts in the blood peaked on the 10th day of admission to 34%. One week later, the patient was completely free of symptoms. The initiation of menthol cigarette use in this patient is the likely reason for ensuing acute eosinophilic pneumonia, hence adding to the sporadic reports on the role of menthol-flavored cigarettes. This case emphasizes a greater reliance on risk factors, as opposed to eosinophilic markers, for the diagnosis and treatment of acute eosinophilic pneumonia to prevent subsequent respiratory failure and intubation in such patients.